Типологічна варіабельність комплексів геометричних мікролітів третьої пачки шарів стоянки Грот Скелястий - Манько, В.О. (Археологический альманах, 2009)
This article is devoted to the analysis of geometrical microliths of Skalisty Rock-shelter, Unit III. Besides it, the comparative analysis of geometrical microliths of Skalisty Rock-shelter with microliths of Zimovniky and Osokorovka-Rogalik industries is carried out. The type-lists of geometrical microliths of specified industries and their statistical analysis are published. The artefacts originated from Skalisty Rock-shelter, Unit III are subdivided on two Late Palaeolithic industries: Shan-Koba and Tavbodrakian.